Factors Affecting Career Choice of Business Students in the Senior High Schools: A Study of Selected Schools in the Cape Coast Metropolis - Archison Duku, John; Bosu, Leticia; Ekow Ansah, Dominic; Achiaa Agyapong, Abigail; Afia Bafowaah, Abigail; Kobina Drokow, Ebenezer; Arboh, Francisca (Naše gospodarstvo/Our economy, 2021)
Factors affecting business students’ choice of career in accounting and factors affecting business students’ inability to choose a career in accounting remains unclear. We used SPSS to analyze data collected from four randomly selected senior high schools in the central region of Ghana through questionnaires. This paper investigated the influences of job opportunities, personal interest, family influence, social status, peer influence, salary expectation, weakness in mathematics, time it takes to become an accountant, and stress involved in the accounting career. The paper then revealed the effects of these in-fluencing factors. Though other factors were found to have substantial effects, the results clearly shows that high salary expectation and job opportunities are the most influential factors that influences a business student’s choice to choose or not to choose a career in accounting. These results could be used as a reference for educational reforms and career counselling.
Keywords: business students; career choice; influential factors; Senior High Schools; Ghana